New State Service of Ukraine: the concept, features and principles - Гончарук, Степан Тихонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article analyzes the concept, characteristics and principles of public service under the new legislation of Ukraine, as well as reviewing other novels of this service based on European standards. Among the reformation transforms multifaceted system of national legislation is important to reform the legal regulation of public service as a fundamental state institutions. 10 December 2015 based on the advanced experience of foreign countries in public-service relations in Ukraine adopted a new law "On civil service". It in a new way defines the concept, principles, legal and institutional framework for the implementation of public services oriented towards citizens in the interests of the state and society. The law greatly expands the concept of public service, will detail the features and content. This service defines how public, professional, politically impartial activities not only on practical tasks and functions of the state, implementation of state policy, but the development and formation of such a policy. The term public servant means a citizen of Ukraine, who holds the position of public service in state body, receives a salary from the state budget and carries out established for this position of authority directly related to the tasks and functions of the public authority and adheres to the principles of public service. The new act compared with the previous more successfully and succinctly interprets the name and content of the principles of public service. Otherwise determined by the classification of posts of civil servants. Establishes three categories of civil service positions, including: 1) category "a" (the highest body of the public service), the posts of top managers in the public service; 2) category "B" – middle; 3) category "B" – all other posts in the public service. For these categories the law defines the corresponding nine ranks of civil servants as a form of special titles that they are assigned. Provided the widespread vacant civil service positions on a competitive basis, fixed a number of other progressive initiatives in this important sphere of state activity.